Surfactant modification of durian peels for removal Remazol Brilliant Orange 3R (RB03R) dye from aqueous solutions: a column studies / Intan Nureleiza Fadhlina Kamaruddin - Kamaruddin, Intan Nureleiza Fadhlina (2019)
The feasibility of durian peel as a non-conventional low cost adsorbent for the removal of Remazol Brilliant Orange 3R (RB03R) was investigated. In this study, durian peel had been chemically modified by cationic surfactant cetylpyridinium chloride monohydrate (CPC) for the removal of Remazol Brilliant Orange 3R (RB03R) in a continuous adsorption process on a fixed-bed column. The surfactant modified durian peel (SMDP) was found to be an efficient media for the removal of dye from wastewater. Bulk density and pH all seem to play important roles in the adsorption of Remazol Brilliant Orange 3R (RB03R). Scanning electron microscopy (SEM) micrograph showed raw durian peel (RDP) have elongated fiber line with small pores while surfactant modified durian peel (SMDP) showed crater-like-holes with large pore space that increase active binding site on SMDP surface and improve adsorption processes. According to FTIR analysis, a successful impregnation of CPC onto the surface of durian peel was presented at peak of 2853 cm'1 on surfactant modified durian peel (SMDP) showed C-H vibration of carbonyl group bands originated from CPC. At peak 3369 cm"1 on SMDP indicate the O-H group in cellulose. All important functional group such as carbonyl and hydroxyl on durian peel surface improve its performance as adsorbent in binding and sequestering RB03R dyes from aqueous solution. In column studies, the breakthrough time (tb), exhaustion times (texh) and dye removal efficiency depend strongly on column parameters which was initial dye concentration, column bed height and flow rate. The breakthrough time (tb), exhaustion time (texh) was proportional to column bed height and inversely proportional to initial dye concentration and flow rate. The dye removal increases from 79% to 99% when the initial concentration of dye solution decreases from 150 mg/L to 25 mg/L. The dye removal increases from 69% to 93% when the column bed height increase from 1 cm to 3 cm. The dye removal increases from 86% to 97% when the influent flow rate decreases from 5 mL/min to 1 mL/min. This study suggests the potential application of durian peel as adsorbents as an alternative to activated carbon can overcome biomass waste problem and sequester dye from colouring wastewater.